The Impacts of SARS-CoV-2 Pandemic on Suicide: A Lexical Analysis - Gonçalves Júnior, Jucier; Sales, Jair Paulino de; Moreno, Marcial Moreira; Rolim-Neto, Modesto Leite (Frontiers in Psychiatry, 2021)
Background: Although COVID-19 is a public health emergency, its consequences for the mental health of the population are still scarce. Likewise, its impact on critical situations such as suicide is still poorly explored in the literature. Therefore, this study aimed to analyze in a pioneering way, through lexical and content analysis techniques, the possible impacts of the new COVID-19 pandemic in suicide behavior. Methods: A lexical analysis, whose sample (not probabilistic, i.e. for convenience) was made up with full length papers (abstracts) and short communications, about suicide behavior in COVID-19 pandemic, in PubMed and Virtual Health Library (VHL) carried out following a lexical and content analysis using the software IRaMuTeQ, version 0.7 alpha 2. Results: The most frequent active words were suicide behavior (n = 649), covid (n = 439), health (n = 358), mental (n = 268), and social (n = 220). Four lexical classes were found and organized into two large groups: the first group, formed by the classes 2 (“Methods for psychological treatment”) and 3 (“Strategies to minimize the covid-19 impacts”) was the most representative, totaling 50.6% of the text segments. The latter, formed by classes 1 (“Signs of clinical depression”) and 3 (“COVID-19 pandemic as a public health problem”) with 49.4% of the text segments. Conclusion: Facing suicide behavior, the direct effects of the COVID-19 pandemic as well as the negative feelings and trigger of previous psychiatric illnesses; the measures to deal with pandemic such as social isolation, decrease in the number of professionals, the opening hours of health establishments and decrease in the demand for medications; and competing phenomena such as the spread of fake news and lack of empathy are aggressive and potentiating factors of suicidal ideation.